(untitled) (International Journal of Built Environment and Sustainability, 2025)
Sports facilities are vital community assets, but their success depends on effectively integrating the often-divergent perspectives of architects and sports managers. This study investigates these contrasting perspectives through a mixed-methods approach, combining a comprehensive literature review with bibliometric analysis of publications indexed in the Web of Science. The literature review reveals a thematic divergence: architects prioritize the physical environment (indoor environmental quality, accessibility, long-term functionality), while sports managers emphasize service quality and the overall user experience (customer satisfaction, operational efficiency). The bibliometric analysis confirms this divergence, identifying six distinct research clusters with limited direct connections between them: "User-Centered Facility Management and Performance Evaluation," "Data-Driven Facility Management and Simulation Tools," "Design Quality, Access, and User Satisfaction," "Sustainability and Evaluation in Sports Facilities," "Operational Barriers and Efficiency in Facility Performance," and "Asset Management and Infrastructure-Oriented Facilities." This pattern highlights the disciplinary siloization in sports facility research. This study’s main contribution is to provide empirical evidence of this fragmentation and to underscore the critical need for a more holistic and integrated approach encompassing both architectural design and facility management principles. Bridging this gap will lead to sports facilities that are not only aesthetically pleasing and structurally sound but also functionally effective, user-centered, and ultimately promote greater participation in sport and physical activity.